2016
DOI: 10.17221/294/2016-pse
|View full text |Cite
|
Sign up to set email alerts
|

Residue of bensulfuron methyl in soil and rice following its pre- and post-emergence application

Abstract: Bensulfuron methyl (BSM) is applied in rice to control a wide range of weeds due to low application rate and high efficiency. A study was conducted to evaluate residues of BSM in soil and rice plant at different doses as pre-and post-emergence application in transplanted rice. The quick easy cheap effective rugged safe (QuEChERS) method was evaluated for BSM residue extraction from different matrices. The limit of detection and limit of quantification was 0.005 and 0.01 µg/g, respectively in soil and rice plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It can be uptaken by weeds and translocated to target sites to inhibit the acetolactate synthase, block biosynthesis of branched-chain amino acids, and finally result in growth inhibition, chlorosis, and necrosis 3,4 . The solubility of BSM is very low (12–120 mg L −1 in water at pH 6.0–7.0 and 25 °C) 5,6 . It was reported that the herbicide was immobile to moderately mobile in soils and easy to be adsorbed by soil particles 68 .…”
Section: Introductionmentioning
confidence: 99%
“…It can be uptaken by weeds and translocated to target sites to inhibit the acetolactate synthase, block biosynthesis of branched-chain amino acids, and finally result in growth inhibition, chlorosis, and necrosis 3,4 . The solubility of BSM is very low (12–120 mg L −1 in water at pH 6.0–7.0 and 25 °C) 5,6 . It was reported that the herbicide was immobile to moderately mobile in soils and easy to be adsorbed by soil particles 68 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the half lethal doses(LD 50 ) of four herbicides in rats are all over 5000 mg/kg according to the Pesticide Manual [19], the four herbicides are extensively used in paddy fields in consideration of good selectivity, high efficiency, and low toxicity. Previous studies primarily concentrated on herbicidal activity and residue levels of four herbicides in rice cropping systems [10,20,21]. The results indicated that pyrazosulfuron-ethyl, bensulfuron-methyl, acetochlor and butachlor were safe and the residues in rice were lower than the maximum residue limit (MRL) at the recommended dosage [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies primarily concentrated on herbicidal activity and residue levels of four herbicides in rice cropping systems [10,20,21]. The results indicated that pyrazosulfuron-ethyl, bensulfuron-methyl, acetochlor and butachlor were safe and the residues in rice were lower than the maximum residue limit (MRL) at the recommended dosage [19,20]. However, weed resistance to these four herbicides increased gradually due to widespread use in paddy fields, which inevitably increased the dosage of these four paddy herbicides [22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Glyphosate was extracted and analysed, as detailed by Brindhavani et al (2020), using HPLC. The extraction and detection method was validated by performing recovery studies before analysing unknown samples, as described by Janaki et al (2016) for bensulfuron methyl.…”
Section: Methodsmentioning
confidence: 99%